Succinate metabolism: underlying biological mechanisms and emerging therapeutic targets in inflammatory bowel disease - Dai, Mingzhu; Bu, Shu; Miao, Zhiwei (Frontiers in Immunology, 2025)
The global incidence of inflammatory bowel disease (IBD) continues to rise, yet its precise pathogenesis remains incompletely understood. In recent years, various gut microbiota-derived metabolites have been implicated in the development of IBD. Among them, succinic acid is a key metabolite produced by intestinal flora and serves as a central intermediate in the tricarboxylic acid (TCA) cycle, which plays a pivotal role in the IBD pathogenesis by modulating the intestinal mucosal barrier function, immune-metabolic reprogramming and cellular energy homeostasis. Abnormal succinate metabolism has also been linked to a range of metabolic disorders, including hepatitis, arthritis, diabetes mellitus, and cardiovascular diseases. Recently, its role in IBD has attracted growing interest. This review systematically elucidates the mechanisms by which succinate promotes pro-inflammatory immune phenotypes through a multifaceted network involving macrophage polarization, T-cell metabolic reprogramming, and epithelial-immune cell interactions, largely mediated via the SUCNR1 signaling axis. Furthermore, we explore the therapeutic potential of targeting succinate metabolism, offering new insights into IBD prevention and treatment.